Neuroanatomical correlates of attitudes toward suicide in a large healthy sample: A voxel-based morphometric analysis. (8th January 2016) - Liu, Huijuan; Wang, Yongchao; Liu, Wei; Wei, Dongtao; Yang, Junyi; Du, Xue; Tian, Xue; Qiu, Jiang
Abstract: Previous studies have indicated that permissive attitudes toward suicide are positively associated with mental illness (e.g., depression and loneliness). Evidence suggests that there are abnormalities in the cognitive and brain functioning of suicidal patients. Nevertheless, there has been no evidence of the correlation between attitudes toward suicide and abnormal brain structure variations in healthy people. Therefore, in this study, we seek to investigate the neuroanatomical differences in healthy participants with regard to attitudes toward suicide. The results show that permissive attitudes toward suicide were significantly correlated with gray matter volume (GMV) in the left dorsolateral prefrontal cortex (DLPFC) and the left cerebellum in the large sample ( n =405), which may be related to inefficient inhibitory control of negative emotion. Then, in a subset of healthy individuals with permissive attitudes ( n =113), we also observed that stronger permissive attitudes toward suicide were positively related to the larger GMV in the left DLPFC and the left middle temporal gyrus (MTG), which may be associated with sensitivity of emotional feeling. Furthermore, loneliness had a mediating effect on the relation between the DLPFC volume and attitudes toward suicide. Taken together, neuroanatomical differences in healthy participants with permissive attitudes toward suicide may provide a better understanding of permissive attitudes toward suicide as a likely risk factor for suicidal behavior. Highlights: We examine the anatomical differences underlying different attitudes toward suicide. Individuals with permissive suicidal attitude exhibits greater GMV in the left DLPFC. Individuals with permissive suicidal attitude exhibits greater GMV in the left MTG. Loneliness mediating the relation between the DLPFC and attitudes toward suicide.